1998
DOI: 10.1046/j.1471-4159.1998.70020794.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Inhibition of Brain Succinate Dehydrogenase by 3‐Nitropropionic Acid Is Sufficient to Initiate Striatal Degeneration in Rat

Abstract: Chronic inhibition of succinate dehydrogenase (SDH) by systemic injection of the selective inhibitor 3nitropropionic acid (3NP) has been used as an animal model for Huntington's disease(HD). However, the mechanisms by which 3NP produces lesions in the striatum are not fully characterized. A quantitative histochemical method was developed to study the level of regional SDH inhibition resulting from intraperitoneal injection of 3NP or chronic intoxication using osmotic pumps. The results showed that (a) 3NP was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
130
0
10

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 198 publications
(152 citation statements)
references
References 31 publications
12
130
0
10
Order By: Relevance
“…The present FDG studies demonstrate that the sensitivity and temporal (Ϸ1 s) and spatial resolution (0.8 mm with 18 F-radiolabeled tracers) of the ␤-MICROPROBE system permits the quantitative assessment of even modest changes in regional metabolic activity in individual rats.…”
Section: Anaesthetized Ratsmentioning
confidence: 70%
See 2 more Smart Citations
“…The present FDG studies demonstrate that the sensitivity and temporal (Ϸ1 s) and spatial resolution (0.8 mm with 18 F-radiolabeled tracers) of the ␤-MICROPROBE system permits the quantitative assessment of even modest changes in regional metabolic activity in individual rats.…”
Section: Anaesthetized Ratsmentioning
confidence: 70%
“…Semiquantitative measurement of succinate dehydrogenase inhibition was performed as described (18). The images of each section were acquired with CYTOSTAR (IMSTAR) and quantified as reported (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the occurrence of mitochondrial dysfunction in brains from Huntington disease (HD) patients, namely, through the inhibition of respiratory chain complexes II and III (Browne et al, 1997;Gu et al, 1996). Systemic administration of the mitochondrial toxin 3-nitropropionic acid (3-NP), an irreversible inhibitor of succinate dehydrogenase, was shown to elicit behavioral abnormalities and cortical and striatal neuronal degeneration in rats and nonhuman primates, similar to that seen in humans with HD (Beal et al, 1993;Brouillet et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, chronic systemic administration of 3NP in rats and non-human primates produces homogenous blockade of complex II within the brain (17), leading to preferential excitotoxic striatal degeneration associated with behavioral abnormalities that are highly reminiscent of HD (18 -20).…”
mentioning
confidence: 99%